Global halal industry: realities and opportunities - Azam, Md. Siddique E.; Abdullah, Moha Asri (Fakultas Ekonomi, Universitas Islam Sultan Agung, 2020)
The global Halal industry as a whole is estimated to worth around USD2.3 trillion (excluding Islamic finance) a year, is now one of the fastest growing markets. Simultaneously, the global market growth is estimated to reach at an annual rate of 20 percent per annum. The Halal industry is no longer confined to food and food-related products. This paper attempts to examine the current realities of the global halal industry by observing the factors determining such increasing demand for Halal industry in addition to the opportunities that are offered fromrecent global development in the market. To achieve the objectives of the study, a methodology of analyzing secondary data from different sources was adopted in this paper. The findings show that there are three major factors driving the rapidly growing global halal market. First, sizable and growing Muslim population at 1.8 per cent per annum, Second, growing economic development and hence increasing purchasing power among the Muslim. The last is the potential halal market in non-Muslim nations and halal industry players. As a way forward, industry players need to deepen knowledge and understanding of the Muslim market (pattern and behavior), regularly update data, and exploit untapped market niches as well as product sales and promotion. Findings and recommendations of this work will be a great resource for future researchers and scholars in relevant areas as well as policy makers to make their strategic decisions in the fields of Halal Industry.